Peran Perawat Pelaksana dengan Gangguan Mental Emosional dalam Penanganan Covid-19 - Aisyah; Giri Widakdo; Naryati; Siti Nurbaya; Mita Mahliyati (HEALTH CARE: JURNAL KESEHATAN, 2023)
One of the impacts of the problems caused by the pressure and stress that takes place continuously on nurses in health care facilities, can result in the emergence of mental emotional emotional and behavioral disorders. worsens the body's resistance, and makes it vulnerable to also being infected with Covid-19. This study aims to find the relationship between the role of the nurse practitioner and Mental Emotional Disorders in Handling Covid 19. This research is an analytical descriptive study with a retrospective cohort design which is a research design that captures an event and its effects at a previous time. The statistical test that researchers will use is Multiple Logistic Regression Analysis. The results showed that bivariate analysis of the role of nurses and co-variates with mental emotional disorders, it can be seen that the variables of the nurse's role, gender and having been exposed to Covid gave significant results with mental emotional disorders with a p value <0.05. in the role of nurse, katim has a greater chance (OR 1.97) of experiencing mental emotional disorders. besides that, male gender (OR 2.53) and people who have never been exposed to covid (OR.1.09) also have the same opportunity to experience emotional mental disorders.